DETERMINANTS OF FARMERS’ PARTICIPATION IN FARM SETTLEMENT SCHEME IN LAGOS STATE, NIGERIA: LESSONS FOR FUTURE RURAL DEVELOPMENT PROGRAMME - Obayelu, Abiodun Elijah; Fabanwo, James Oladipupo (Journal of Agricultural Sciences (Belgrade), 2020)
In its determination to provide food and jobs for Nigerians, and appeal to educated young men to set the pattern for farming, many state governments have re-introduced Farm Settlement Scheme (FSS) / Graduate Employment Scheme once abandoned. One major challenge leading to programmes failure in Nigeria is the inability to know the influencing the factors to participations and constraints of such programmes. This study analysed the determinants of crop farmers’ participations in FSS in Lagos State with the aim of drawing some lessons for future rural development programme. One hundred and thirty (130) farmers were sampled through a two-stage sampling procedures. Data were collected with the aid of questionnaire and were analysed using both descriptive and inferential statistics such as the logit regression model. Results showed that about 67% of the respondents were male and 72% were married with mean farm size of 2.6ha (58%). The major constraining factors by farmers to participation in FSS were administrative bottlenecks, inadequate capital, and government interference. The logit regression showed that educational level farming experience, extension contacts and security of land under FSS were the significant variables (P